Optimization Of Palm Oil Mill Effluent Treatment By Applying RSM And ANN - Muhammad Said; Muneer M Ba-Abbad; Abdul Wahab Mohammad (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
AbstractThe optimization of the COD removal from palm oil mill effluent (POME) has done. The correlation of concentration and pH of POME, and Trans membrane pressure (TMP) of Reverse Osmosis (RO) membrane was optimized by response surface method using a second order polynomial model with Box Behken design consist of 17 runs. To determine whether the model was adequate for representing the experimental data; it was indicated by the ANNOVA table (p-value, lack of fit and R2 values). The main factor influenced the COD removal was concentration and pH of POME. The optimum conditions were determined from 3D response surface and 2D contour graphs i.e. 28.30% of POME concentration at pH 10.75 and TMP 0.69 kPa to yield 24.1372 mg/L of COD value. The results demonstrate that the response surface method effective to minimize the number of experiment. Keywords: POME; RO membrane; RSM; ANN; COD